Compressive and Flexural Tests on Adobe Samples Reinforced with Wire Mesh - Jokhio, Gul A.; Al-Tawil, Y. M.Y.; Sharifah Maszura, Syed Mohsin; Gul, Yasmeen; Noram Irwan, Ramli (IOP Publishing Ltd, 2018)
Adobe is an economical, naturally available, and environment friendly construction material that offers excellent thermal and sound insulations as well as indoor air quality. It is important to understand and enhance the mechanical properties of this material, where a high degree of variation is reported in the literature owing to lack of research and standardization in this field. The present paper focuses first on the understanding of mechanical behaviour of adobe subjected to compressive stresses as well as flexure and then on enhancing the same with the help of steel wire mesh as reinforcement. A total of 22 samples were tested out of which, 12 cube samples were tested for compressive strength, whereas 10 beams samples were tested for modulus of rupture. Half of the samples in each category were control samples i.e. without wire mesh reinforcement, whereas the remaining half were reinforced with a single layer of wire mesh per sample. It has been found that the compressive strength of adobe increases by about 43% after adding a single layer of wire mesh reinforcement. The flexural response of adobe has also shown improvement with the addition of wire mesh reinforcement.